Robust Trajectory-Tracking Control of a Rotorcraft Using Immersion-and-Invariance-Based Adaptive Backstepping Control - Yoo-Seung Choi; Il-Ryeong Lee; Jun-Young An; Moon-Gyeang Cho; Chang-Joo Kim (International Journal of Aerospace Engineering)
This paper investigates an adaptive backstepping control based on the immersion-and-invariance (I&I) method for a rotorcraft’s trajectory-tracking control problem. To effectively cope with both parametric uncertainties and external disturbances affecting all forces and moments of a rotorcraft, the I&I-based disturbance observer is designed and combined with an adaptive backstepping controller. During the design process, a simple form of the observer structure is suggested, and the performance of the observer is analyzed using a candidate Lyapunov function. Then, the closed-loop stability of the adaptive controller is analyzed for both time-invariant and time-varying disturbances. Additionally, the tuning function-based adaptive backstepping controller is designed and used to investigate the outperformance achievable with the proposed method. Finally, comparative simulation results using a high-fidelity rotorcraft math model is provided to show the effectiveness of the proposed strategy.